A Critique on the Book Descartes to Leibniz: A History of Philosophy - Abdurrazzaq Hesamifar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book entitled A History of Philosophy written by Fredrick Copleston. This set of books is the main source of teaching history of philosophy in the departments of philosophy at the universities of the country and its volumes have been translated into Persian by some experts in philosophy. Two volumes of this set are dedicated to the Modern philosophy of the 17th and 18th centuries: Vol. 4 about Rationalism and vol. 5 about Empiricism. In vol. 4, after a comprehensive introduction in which the general specifications of the modern period have been explained, Copleston has discussed the ideas of the modern rationalists notably Descartes, Pascal, Malebranche, Spinoza, and Leibniz. The important advantages of the book are having the educative form and containing the main ideas of any one of those philosophers. The translator and editor of the book are well-known experts in philosophy, but because of the careless publication of the book, the book contains a lot of formal and contextual mistakes which have not been removed by publishers after several publications. Evaluating the content of the book, this article tries to refer to some defects of it.